2013
DOI: 10.7150/ijms.6395
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sperm Fertility Related Proteins

Abstract: Infertility is an important aspect of human and animal reproduction and still presents with much etiological ambiguity. As fifty percent of infertility is related to the male partner, molecular investigations on sperm and seminal plasma can lead to new knowledge on male infertility. Several comparisons between fertile and infertile human and other species sperm proteome have shown the existence of potential fertility markers. These proteins have been categorized into energy related, structural and other functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 69 publications
(104 reference statements)
2
44
0
2
Order By: Relevance
“…The presence or absence (Soggiu et al, 2013) and abundance (Somashekar et al, 2015) of particular proteins might affect spermatozoa fertilizing ability, but the role of a single protein in regulating fertilization process needs to be firmly established. So far, many fertility signature proteins have been identified in bovine (Peddinti et al, 2008) and in human (Ashrafzadeh et al, 2013). The importance of major sperm proteins such as binder of sperm proteins (BSP) (Plante et al, 2014;Somashekar et al, 2015), heparin binding proteins (Arangasamy et al, 2005), CatSper (Singh & Rajender, 2014), and osteopontin (Monaco et al, 2009) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence (Soggiu et al, 2013) and abundance (Somashekar et al, 2015) of particular proteins might affect spermatozoa fertilizing ability, but the role of a single protein in regulating fertilization process needs to be firmly established. So far, many fertility signature proteins have been identified in bovine (Peddinti et al, 2008) and in human (Ashrafzadeh et al, 2013). The importance of major sperm proteins such as binder of sperm proteins (BSP) (Plante et al, 2014;Somashekar et al, 2015), heparin binding proteins (Arangasamy et al, 2005), CatSper (Singh & Rajender, 2014), and osteopontin (Monaco et al, 2009) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Processes such as capacitation, hyperactivation, acrosome reaction, motility, zona pellucida binding and membrane fusion are governed by phosphorylation (Ashrafzadeh et al. ).…”
Section: Protein Phosphorylation and Kinasesmentioning
confidence: 99%
“…During spermatogenesis the chromatin undergoes extensive remodeling where most histones are replaced with protamines resulting in a very condensed chromatin structure where most genes are inaccessible to the transcription machinery and therefore silenced. The current belief is that no, or very little, nuclear transcription and translation occur in sperm; hence, peripheral proteins and posttranslational modifications play major roles in sperm function (1)(2)(3).…”
mentioning
confidence: 99%
“…The function of these spermatozoa depends on complex orchestrated biologic reactions controlled by various proteins. Any defect within these multistep processes can result in infertility or subfertility (1). During spermatogenesis the chromatin undergoes extensive remodeling where most histones are replaced with protamines resulting in a very condensed chromatin structure where most genes are inaccessible to the transcription machinery and therefore silenced.…”
mentioning
confidence: 99%